Multiple Intelligences in Elementary Science Education: Impact of Guided Discovery Approach on Learning Interest - Dela Galuh Thamkaniah; Ari Suryawan; Ali Mustadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Science education at the elementary school level often ignores the process dimension, emphasizing more on the final product of knowledge. This study aims to analyze the effect of Guided Discovery Learning model on students' interest in developing multiple intelligence-based basic science learning. Using a pre-experimental design, 27 sixth semester students from the Elementary School Teacher Education program participated with purposive sampling. Data collection included observation, questionnaires, tests, and documentation, with data analyzed using descriptive statistics and t-test. The results showed a significant difference before and after the application of Guided Discovery model in the classroom. So it can be concluded that, the Guided Discovery Learning model has a significant impact on student learning interest in the development of multiple intelligence-based basic science learning. This research provides evidence that guided discovery learning and constructive feedback is an effective strategy to improve learning quality and students' interest in learning. This model not only increases students' interest in learning but also promotes critical thinking and problem-solving skills.